Identification, evaluation and selection of a bacterial endophyte able to colonize tomato plants, enhance their growth and control Xanthomonas vesicatoria, the causal agent of the spot disease. Issue 2 (4th March 2022) - Vurukonda, Sai Shiva Krishna Prasad; Giovanardi, Davide; Stefani, Emilio
Abstract: Beneficial endophytes are key factors in plant productivity and disease control; therefore, research is ongoing to characterize the potential of endophytes as microbial inoculants to promote plant growth and act as biocontrol agents. In this study, we searched for and identified a set of endophytes occurring naturally in a few important crops. Beneficial endophytes were shown to antagonize several important fungi and bacteria, in particular those affecting tomato ( Solanum lycopersicum ), including Rhizoctonia solani, Alternaria alternata, Clavibacter michiganensis pv. michiganensis, Ralstonia solanacearum, and Xanthomonas vesicatoria . We characterized the most promising as potential inoculants of tomato, aiming to foster plant growth and control the bacterial spot disease caused by Xanthomonas vesicatoria . Among the selected endophytes, we identified a novel streptomycetes, taxonomically related to Streptomyces avermitilis and a pseudomonad, identified as Pseudomonas granadensis . The beneficial effects of these two bacteria, used as single inoculants or as a combination of both, were seen in a significant increase in root and shoot length (approximately 31% and 34% for the streptomycetes and 18% and 16% for the pseudomonad) and dry root biomass (90% for the streptomycetes and 70% for the pseudomonad). Additionally, both inoculants reduced disease progression and severity following inoculation with X. vesicatoria . There was no significant difference between plants treated with single inoculants and plants treated with both. The penetration and efficient colonization of tomato tissues by a green fluorescent protein-tagged culture of the streptomycetes was observed by confocal microscopy, confirming its endophytic nature.